Validation of a vision-screening tool for use by nurses and other non-eye care health practitioners on stroke survivors. Issue 4 (4th July 2022) - Courtney-Harris, Michelle; Jolly, Neryla; Rowe, Fiona; Rose, Kathryn
Abstract : Purpose : To validate a vision-screening tool for use by nurses and other non-eye care health practitioners (NECHP) to aid identification of visual deficits and ocular conditions in stroke survivors. Material and Methods : Stroke survivors were recruited from two metropolitan Sydney public hospitals who had no access to on-site eye care professionals. Those admitted for 3 days and who were able to provide clear responses were randomly allocated into two groups. All were assessed by a NECHP using a purposely designed bedside vision-screening tool to assess their visual function. In Group 1, the orthoptist repeated the assessment with the same vision-screening tool, in Group 2 they performed a comprehensive orthoptic assessment. Levels of agreement and sensitivity and specificity for key outcomes were assessed. Findings : Levels of agreement for most items analyzed for Group 1 reached 80%. Comparison of the screening tool to a comprehensive orthoptist assessment (Group 2), demonstrated high (88.57–91.12%) sensitivity and specificity for detecting pre-existing and acquired visual problems. Conclusion : The vision-screening tool is a valid instrument for use by NECHP, for the detection of vision defects in stroke survivors. Improved detection of eye conditions may facilitate timely identification and management of visual conditions in stroke survivors, potentially improving patient care and rehabilitation outcomes.